Study Korelasi Faktor-Faktor Yang Berhubungan Dengan Kualitas Hasil Belajar Melalui Orientasi Masa Depan Pada Mahasiswa Politeknik Kesehatan Surakarta Tahun 2017 - Dodiet Aditya Setyawan; Wiwik Setyaningsih; Ari Sarwanto (Poltekkes Kemenkes Surakarta, 2019)
Background: Achieving a good quality of a student’s learning outcomes is influenced by many factors including intelligence, talent, interest and attention, motivation, ways and habits of learning, family and school environment. That is why the level of Intelligence Quotient (IQ) is not the only factor that determines one's success, because there are other influencing factors. This study aimed to determine the factors that influenced the quality of students' learning outcomes at Politeknik Kesehatan Surakarta. Method: This study was a correlational descriptive study which is explanatory in nature that explains the relation between study variables through hypothesis testing. The approach method used in this study was cross sectional. This research was conducted in Politeknik Kesehatan Surakarta environment which consisted of 8 Departments with a total of 3,407 students. The sampling technique used to determine the number of samples in this study was Proportional Stratified Random Sampling, with a sample size of 358 respondents. While the data analysis plan was done descriptively, bivariate with Kendall's Tau technique. Results : The results of the study show that the factors which are proven to be significantly related to the students’ learning outcomes quality in Politeknik Kesehatan Surakarta are Spiritual Intelligence (p = 0.019); Motivation (p = 0.031), Learning Habits (p = 0.037). Conclusion. Factors that are significantly related to the quality of learning outcomes in Politeknik Kesehatan Surakarta students include Spiritual Intelligence, Motivation, and Learning Habits. While the Spiritual Intelligence factor is not significantly related to the quality of students' learning outcomes at Politeknik Kesehatan Surakarta.